2021
DOI: 10.1042/bsr20204005
|View full text |Cite
|
Sign up to set email alerts
|

Revealing mechanism of Caulis Sargentodoxae for the treatment of ulcerative colitis based on network pharmacology approach

Abstract: Objective: The traditional Chinese medicine Caulis Sargentodoxae is widely used in the treatment of ulcerative colitis (UC), but the mechanism remains unknown. The present study aims to reveal its effective components, targets and pathways through network pharmacology and bioinformatics approaches. Materials and methods: Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) was used to identify effective components. The ligand-based targets prediction was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…In the study of the molecular mechanism of the therapeutic effect of Caulis Sargentodoxae on ulcerative colitis, eight active components play a significant role and involve 102 key targets, which are closely related to the positive regulation of cell vitality, reaction to toxic substances, leukocyte migration, cell response to drugs, and inflammatory response. It was confirmed that the PI3K-Akt signaling pathway and HIF-1 signaling pathway are key targets of the UC-related signaling pathway ( Liu et al, 2021a ). Sophora flavescens has a certain effect on ulcerative colitis.…”
Section: Application Of Network Pharmacology In the Treatment Of Ulce...mentioning
confidence: 90%
“…In the study of the molecular mechanism of the therapeutic effect of Caulis Sargentodoxae on ulcerative colitis, eight active components play a significant role and involve 102 key targets, which are closely related to the positive regulation of cell vitality, reaction to toxic substances, leukocyte migration, cell response to drugs, and inflammatory response. It was confirmed that the PI3K-Akt signaling pathway and HIF-1 signaling pathway are key targets of the UC-related signaling pathway ( Liu et al, 2021a ). Sophora flavescens has a certain effect on ulcerative colitis.…”
Section: Application Of Network Pharmacology In the Treatment Of Ulce...mentioning
confidence: 90%
“…As a classical signaling pathway, the PI3K-AKT signaling pathway plays a vital role in the diseases. Caulis Sargentodoxae could regulate the PI3K-AKT signaling pathway to exert anti-inflammatory effects [ 40 ]. PI3K could respond to LPS and TNF- α , activate AKT, and affect NF- κ B to produce antiapoptotic and proinflammatory effects [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Through network pharmacology, a multidimensional network model of the actions of drugs on the body can effectively be established, based on single components and the transformation of system control, in line with the holistic thinking of TCM theory. 6 Molecular docking simulations are based on the geometric configurations and forces of molecules to predict interactions between molecules. 7 In recent years, molecular docking technology has been widely used in the screening of pharmacodynamic components of TCM, providing new technical support for the assessment of the effectiveness and safety of TCM and other quality issues.…”
Section: Introductionmentioning
confidence: 99%
“…Network pharmacology is based on bioinformatics and systems biology, combined with the nodes in the biological network and interactions 5 . Through network pharmacology, a multidimensional network model of the actions of drugs on the body can effectively be established, based on single components and the transformation of system control, in line with the holistic thinking of TCM theory 6 . Molecular docking simulations are based on the geometric configurations and forces of molecules to predict interactions between molecules 7 .…”
Section: Introductionmentioning
confidence: 99%